2011
DOI: 10.1007/s00586-011-2055-4
|View full text |Cite
|
Sign up to set email alerts
|

Patients with adolescent idiopathic scoliosis of Lenke type-1 curve exhibit specific pedicle width pattern

Abstract: Introduction Study aim was to find out if patients with Lenke type 1 curve exhibit smaller pedicles and specific pedicle width pattern compared with individuals with no scoliosis. Materials and methods 4,828 pedicle width measurements (T1-L5) in 61 consecutive patients with adolescent idiopathic scoliosis of Lenke type 1 curve, 61 control subjects, and 20 patients with Lenke type 5 curve, were retrospectively performed by an experienced neuroradiologist. Results Among patients with Lenke type 1 curve, the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
(32 reference statements)
2
11
0
Order By: Relevance
“…Pedicle width, being the smallest cross-sectional dimension, is the most important factor as it dictates the maximum pedicle screw diameter that can be accommodated safely without medial or lateral cortical breach. Our study showed clinically relevant smaller pedicle widths (inner and outer cortical) on the concave side periapically-a finding consistent with previous studies using CT, MRI, and cadavers [1,18,21,25,30,35]. Inner and outer cortical pedicle widths were measured to provide clarity over the inconsistencies or ambiguities that existed in the measurement definitions in previous studies [9,36].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Pedicle width, being the smallest cross-sectional dimension, is the most important factor as it dictates the maximum pedicle screw diameter that can be accommodated safely without medial or lateral cortical breach. Our study showed clinically relevant smaller pedicle widths (inner and outer cortical) on the concave side periapically-a finding consistent with previous studies using CT, MRI, and cadavers [1,18,21,25,30,35]. Inner and outer cortical pedicle widths were measured to provide clarity over the inconsistencies or ambiguities that existed in the measurement definitions in previous studies [9,36].…”
Section: Discussionsupporting
confidence: 89%
“…Questions/Purposes To use CT scans (1) to analyze pedicle anatomy in the adolescent thoracic scoliotic spine comparing concave and convex pedicles and (2) to assess the intra-and interobserver reliability of these measurements to provide critical information to spine surgeons regarding size, length, and angle of projection. Methods Between 2007 and 2009, 27 patients with adolescent idiopathic scoliosis underwent thoracoscopic anterior correction surgery by two experienced spinal surgeons.…”
mentioning
confidence: 99%
“… 22 Recently, Abul-Kasim et al studied the pedicle width pattern in Lenke type 1 AIS patients and they reported similar findings. 23 We also found that in the upper thoracic vertebrae, the transverse pedicle width was significantly wider on the concave side which can also be identified as the convex side of the compensatory curve. Abul-Kasim et al also reported a similar pattern in their study.…”
Section: Discussionsupporting
confidence: 56%
“…Interestingly, the observed asymmetry was considerably smaller than previously described. [47][48][49] Additionally, no direct correlation was found between the degree of asymmetry, the magnitude of the Cobb angle, and the amount of rotation of the apex in these moderate to severe AIS curves. In summary, the fact there is almost no asymmetry in the true transverse plane in AIS suggests that asymmetrical growth is not the driver for rotation in AIS.…”
Section: Introductionmentioning
confidence: 99%